Characterization of Activated Carbon from Pyrolysis Process of Bamboo Base Waste (Dendrocalamus asper) - Tunjung Wahyu Widayati; Danang Jaya; Anantyto Danujatmiko (CHEMICA: Jurnal Teknik Kimia, 2020)
Bamboo is one type of grass that is part of non-timber forest products. The chemical properties of bamboo contain cellulose, lignin, pentosan, ash, and silica. To make charcoal from bamboo it is necessary to go through a pyrolysis process. Pyrolysis is a process of thermal decomposition carried out in an inert condition. Pyrolysis gradually encourages the formation of secondary reactions, where after a process occurs, recombination occurs which will produce secondary charcoal. Pyrolysis at high temperatures can cause activated charcoal, which is caused by cracking on the surface of the charcoal thereby increasing the surface area of the charcoal. BET analysis is needed to find out the adsorption power of gas molecules on the surface and to the basis for analysis techniques that are important in the measurement of a certain surface area of the material. The ability of activated charcoal to absorb liquid N2 is carried out at 77K with the GSA Quantachrome NovaWin. The largest surface area was obtained in this study at a temperature of 800 Â°C with pyrolysis time for 3 hours which resulted in a surface area value of 343.9424 m2/g of activated carbon. Based on this research, it can be concluded that higher temperatures and the longer pyrolysis time of pyrolysis, the higher value of the surface area that is produced at a certain temperature and time until the carbon pores are damaged.